The role of interleukin-17 and interleukin-23 inhibitors in the development, progression, and recurrence of cancer: A systematic reviewCapsule Summary - Marie Vangilbergen, MD; Aline Stockman, MD; Axelle Van De Velde, MD; Maria Garmyn, MD, PhD; Kevin Punie, MD, PhD; Tom Hillary, MD, PhD (Elsevier, 2024)
Background: Biologicals targeting interleukin (IL)-17 and IL-23 improve quality of life in psoriasis and other chronic autoimmune disorders with a favorable safety profile. However, current guidelines do not recommend their use in patients with recent oncologic history due to limited evidence. Objective: To understand the impact of IL-17 and IL-23 inhibitors on cancer development, progression, and recurrence by systematically reviewing available literature. Methods: We conducted a systematic review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Results: Most studies investigating the use of IL-23 and IL-17 blockers did not find a higher incidence of cancer compared to the general population. One study observed no relapse in patients with a history of cancer. Limitations: The systematic review is limited due to variations in study designs and outcomes, making it difficult to achieve a comprehensive synthesis and comparison between studies. Furthermore, small sample sizes were notable. Conclusion: Preclinical studies suggest that treating psoriasis with IL-17 or IL-23 blockers is safe, also in patients witch active cancer or a history of it. Pharmacovigilance data show no increased malignancy rate in patients treated with these treatment modalities. However, data on relapse in patients with a history or active malignancy are limited.